2013
DOI: 10.1387/ijdb.130193jg
|View full text |Cite
|
Sign up to set email alerts
|

Pitx3 directly regulates Foxe3 during early lens development

Abstract: Pitx3 is a bicoid-related homeodomain transcription factor critical for the development of the ocular lens, mesencephalic dopaminergic neurons and skeletal muscle. In humans, mutations in PITX3 are responsible for cataracts and anterior segment abnormalities of varying degree; polymorphisms are associated with Parkinson's disease. In aphakia (ak) mice, two deletions in the promoter region of Pitx3 cause abnormal lens development. Here, we investigated systematically the role of Pitx3 in lens development includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 58 publications
(53 reference statements)
6
28
0
Order By: Relevance
“…The spontaneous mutation aphakia (ak) is recessive and causes a small eye phenotype with the absence of lens and eyelids (Grimm et al, 1998;Varnum & Stevens, 1968). Pitx3 was mapped near the ak locus on mouse chromosome 19 and its expression was absent in ak/ak homozygous mutant lens (Semina et al, 1997(Semina et al, , 2000 (Ahmad et al, 2013). Interestingly, pitx3 knockdown in zebrafish results lens and retina defects and in reduced foxe3 lens expression (Shi et al, 2005(Shi et al, , 2006), suggesting that PITX3 mediated regulation of FOXE3 is conserved in vertebrates.…”
Section: Pitx3 Animal Models and Mechanistic Insights Into The Patholmentioning
confidence: 99%
“…The spontaneous mutation aphakia (ak) is recessive and causes a small eye phenotype with the absence of lens and eyelids (Grimm et al, 1998;Varnum & Stevens, 1968). Pitx3 was mapped near the ak locus on mouse chromosome 19 and its expression was absent in ak/ak homozygous mutant lens (Semina et al, 1997(Semina et al, , 2000 (Ahmad et al, 2013). Interestingly, pitx3 knockdown in zebrafish results lens and retina defects and in reduced foxe3 lens expression (Shi et al, 2005(Shi et al, , 2006), suggesting that PITX3 mediated regulation of FOXE3 is conserved in vertebrates.…”
Section: Pitx3 Animal Models and Mechanistic Insights Into The Patholmentioning
confidence: 99%
“…TFAP2A has been shown to be responsive to retinoic acid, to inhibit the WNT pathway (Li and Dashwood 2004) and be involved in PITX2 regulation (Bamforth et al 2004). PAX6 deficiency has been shown to negatively affect FOXE3 (Blixt et al 2007) and PITX3 expression (Chauhan et al 2002); PITX3 has been reported to directly regulate FOXE3 expression (Shi et al 2006; Ahmad et al 2013). PAX6 and TFAP2A have been demonstrated to physically interact and promote transcription of some corneal genes (Sivak et al 2004).…”
Section: Figmentioning
confidence: 99%
“…This mutation lets the homeodomain intact, but more than the half of the C-terminal part (including the OAR region) is lost (Wada et al, 2014). In the developing lens, Foxe3 is a direct target gene of PITX3 (Ahmad et al, 2013).…”
Section: Eye and Parkinson's Disease: Pitx3mentioning
confidence: 99%